Transforming Vietnamese Agriculture : Gaining More for Less - World Bank Group (World Bank, Washington, DC, 2016)
Over the past quarter century, Vietnam’s agricultural sector has made enormous progress. Vietnam’s performance in terms of agricultural yields, output, and exports, however, has been more impressive than its gains in efficiency, farmer welfare, and product quality. Vietnamese agriculture now sits at a turning point. The agricultural sector now faces growing domestic competition - from cities, industry, and services - for labor, land, and water. Rising labor costs are beginning to inhibit the sector’s ability to compete globally as a low cost producer of bulk undifferentiated commodities. Going forward, Vietnam’s agricultural sector needs to generate more from less. That is, it must generate more economic value - and farmer and consumer welfare - using less natural and human capital and less harmful intermediate inputs. The strategic shift was highlighted in the government’s agricultural restructuring plan (ARP), approved by the Prime Minister in June 2014. The ARP defines sector goals in terms of the triple bottom line of economically, socially, and environmentally sustainable development. It lays out expected changes in the roles and spending patterns of the government in the sector and discusses the need to work with other stakeholders, including in the private sector. It calls for an ambitious and ongoing process of learning and experimentation, and several potential directions are offered in this report.